2014
DOI: 10.9784/leb2(1)he.01
|View full text |Cite
|
Sign up to set email alerts
|

A review of the status of the larval parasitoid, <i>Asecodes hispinarum</i> Boucek, and of the pupal parasitoid, <i>Tetrastichus brontispae</i> Ferriere (Hymenoptera: Eulophidae), as biological control agents of the coconut leaf beetle, <i>Brontispa longissima</i> (Gestro) (Coleoptera: Chrysomelidae: Cassidinae), in the Asia-Pacific Region

Abstract: The Coconut Leaf Beetle, Brontispa longissima, endemic to Indonesia and Papua New Guinea, has spread to many countries in Asia and the Pacific region, where it has become a serious pest. Several countries have achieved significant control of B. longissima by releasing and establishing parasitoids, such as Asecodes hispinarum and Tetrastichus brontispae, which attack immature stages of the pest. A review of previous works undertaken on the biological control of the Coconut Leaf Beetle in these countries and els… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…As an invading pest, B. longissima has high risk and great harm. The results showed that most effective measures for comprehensive treatment of B. longissima are to strengthen the quarantine work during the transport of B. longissima host seedlings to prevent their spread, and then use chemical agents [9] or parasitic bees [45] to kill them in the occurrence area.…”
Section: Discussionmentioning
confidence: 99%
“…As an invading pest, B. longissima has high risk and great harm. The results showed that most effective measures for comprehensive treatment of B. longissima are to strengthen the quarantine work during the transport of B. longissima host seedlings to prevent their spread, and then use chemical agents [9] or parasitic bees [45] to kill them in the occurrence area.…”
Section: Discussionmentioning
confidence: 99%